Doctoral students' well-being in United Kingdom business schools: A survey of personal experience and support mechanisms. Issue 2 (July 2021) - McCray, Janet; Joseph-Richard, Paul
Abstract: We present the perspectives on mental well-being of 63 Doctoral students (DS) undertaking a PhD in business schools in United Kingdom (UK) universities. Utilising a cross-sectional survey, the aims of this study are to 1. Capture business and management doctoral students' (DSs) views on their mental well-being and the factors that affect it. 2. Critically review the influence of the business school learning environment on doctoral student well-being. 3. Reflect on the effectiveness of business schools' support for the well-being of doctoral students. Findings indicate that many business school doctoral students viewed their mental well-being negatively and more than half considered their personal well-being as their own problem. Personal and interpersonal factors caused a very high percentage of their negative mental well-being issues, with the majority of research supervisors being viewed as a positive support. However, in business school doctoral training programmes, respondents reported minimal input on managing and understanding their personal well-being, despite research which correlates faculty and departmental support for well-being and PhD completion. In the light of these findings we suggest that individual business schools should review their training curriculum for doctoral students to prevent over-reliance on the supervisory team and offer more formal training on managing mental well-being. Highlights: Many business school doctoral students in the study (n = 32) viewed their own mental well-being negatively. Personal and interpersonal factors caused most of their negative mental well-being issues. Research supervisors were viewed as a positive support. Business school doctoral training programmes, offered minimal input on managing and understanding their personal well-being.